الاتجاهات الحديثة في دراسة المحددات الجيومورفولوجية في نشأة المدن والتوسع العمراني في القرن الحادي والعشرين مع التطبيق على مصر - شيرين صبري السباعي (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
يهتم البحث بتحديد الاتجاهات الحديثة في دراسة المحددات الجيومورفولوجية في نشأة المدن والتوسع العمراني، لما لها من تأثير مباشر على شكل المدينة وتنظيمها، وذلك من خلال تحديد هذه المحددات وتحليلها وتوزيعها، ومن ثم الوقوف على نقاط الضعف والقوة بالنسبة لمعايير تحديدها، حيث تقف في بعض الأحيان عائقا يحدد شكل وامتداد المدن في اتجاهات مختلفة بحيث تنمو في جهه ويتعرقل نموها في جهة أخرى، وتتمثل أهم المحددات المؤثرة في: الخصائص الجيولوجية والتضاريسية، والمناطق الساحلية، والأودية الجافة، والجروف والمنحدرات، والسبخات، والأشكال الرملية، وما ينتج عنها من أخطار، لذا يفيد تطبيق التقنيات الحديثة الأكثر اكتمالا بين أدوات البحث الجغرافي للاستفادة منها في إمكانية التعديل والتقويم لتوجيه المدن، كما يستلزم وضع مجموعة من الخطط والأهداف لتحقيق التنمية العمرانية المستدامة في المناطق الحضرية، خاصةً لأنها تعد أحد الركائز الأساسية لرؤية مصر 2030 تبعاً لأحدث أساليب التخطيط العالمية، وذلك من أجل استيعاب أكبر عدد من السكان، واقتراح بعض الحلول والتوصيات لحل مشكلة الضغط السكاني على منطقة محدودة دون أخرى، لنشر العمران فى ربوع الدولة تحقيقاً للأمن القومي المصري مستقبلا.The research is concerned with identifying recent trends in the study of geomorphological determinants in the emergence of cities and urban expansion, due to their direct impact on the shape and organization of the city. This is conducted by pointing out, analyzing, and distributing these determinants, and then identifying the strengths and weaknesses of the criteria for determining them, as they sometimes become an obstacle that determines the shape and expansion of cities in different directions: they grow in one direction and their growth is hindered in another. The most significant influential determinants are the following: geological and topographical characteristics, coastal areas, arid valleys, cliffs and slopes, salt marshes, sandy forms, and the resulting dangers. Therefore, applying the most complete recent techniques among geographical research tools is useful to benefit from them in the possibility of modifying and reforming to direct cities. It also requires setting a set of plans and goals to achieve sustainable urban development in urban areas, particularly since they are one of the basic pillars of Egypt's Vision 2030 according to the recent global planning methods. This is in order to accommodate the largest number of residents, and to propose some solutions and recommendations to solve the problem of population pressure on a limited area over another so as to spread urbanization throughout the country in order to achieve Egyptian national security in the future.